Sistem Pendukung Keputusan Pemilihan Kafe Terbaik Dengan Menggunakan Metode OCRA - Zebua, Juli Novita Putri (CV. Graha Mitra Edukasi, 2024)
Currently, the development of the culinary business in Indonesia is increasingly rapid. One of them is the cafe business. A cafe is a place to tell stories with friends, friends and family while enjoying dishes such as drinks and food that have been provided by the management according to the menu list available. In North Nias district there are several cafes which are gathering places for visitors who want to tell stories or want to enjoy the dishes available at the cafe. One of the cafes that the tourism department hopes is a cafe that can be enjoyed by all ages, from parents, adults, teenagers and even children. So that visitors who want to go to a cafe with their family can get comfort from each other in the same place. To determine the best cafe, the cafe must meet predetermined criteria, namely taste, price, service, facilities and cleanliness. However, the deciding party in this case is the Tourism Department in choosing the best cafe. So we need a decision making system that can help determine which cafe is the best cafe chosen by the North Nias district tourism office. The method used for the decision support system is the OCRA (Operational Competitiveness Rating Analysis) method. In this research the author applies the OCRA method with ROC weighting. The author will rank this method in order to find out the best alternative in determining the best cafe in North Nias Regency because this method is related to determining the value weight of each existing criterion and is equally used for the value ranking process. So a decision support system (DSS) is needed to solve this problem. SPK can be interpreted as an information system that is used to support decision making in a company or organization. In this research, the Operational Competitiveness Rating Analysis (OCRA) method is used, which is a method that can produce data in selecting the best cafe. The research carried out this by collecting data on selecting the best cafes, then sorting the data according to the criteria and carrying out calculations. And determine the best alternative that deserves to be the best cafe. It is hoped that the results of this research can process the selection of the best cafe in North Nias Regency, this research can make it easier for the tourism office to select the best cafe based on the OCRA method in selecting the best cafe in North Nias Regency. Based on the test results, the best alternative results were obtained, namely Cafe Saito Coffee (A5) which obtained a score of 2.309